Species diversity and soil carbon stock evaluation in mangrove forests of selected barangays, Guiuan, Eastern Samar - Bunani, Kalanie Pearl Joy G.
Mangrove forests are crucial carbon sinks, aiding in climate change mitigation by absorbing and storing atmospheric carbon. Soil within mangrove ecosystems, notably in Guiuan, Eastern Samar, specifically in Brgy. Baras and Brgy. San Antonio, holds significant carbon stocks. This study aimed to establish baseline data on carbon storage in selected mangrove forests in Guiuan, Eastern Samar by determining the species composition, measuring soil carbon stock at various depths and assessing its correlation with soil bulk density across different zones. Sampling encompassed four points per site, distributed across landward, middle, and seaward zones. Soil collection involved a German corer to gather the uppermost 100 cm of soil and then divided it into intervals for analysis. Soil carbon stocks were determined using the Loss on Ignition method. Results revealed that San Antonio stored significantly more carbon (813.75 Mg C/ha) than Baras (601.49 Mg C/ha). Fluctuations in carbon stock across depth suggested carbon gain and loss. Soil bulk density positively correlated with carbon stock, suggesting that the impact of soil bulk density on carbon stock is negligible. Overall, mangrove ecosystems exhibited resilience and carbon sequestration potential, which are essential for local climate change mitigation strategies. Understanding carbon dynamics in mangrove soils is vital for informed conservation and management efforts, emphasizing the role of these ecosystems in global carbon cycling and climate change resilience.